Distant Mirror the calamitous 14th century - Tuchman, Barbara W. (London Penguin Books, 2017)
The fourteenth century reflects two contradictory images: on the one hand, a glittering age of crusades, cathedrals, and chivalry; on the other, a world plunged into chaos and spiritual agony. In this revelatory work, Barbara W. Tuchman examines not only the great rhythms of history but the grain and texture of domestic life: what childhood was like; what marriage meant; how money, taxes, and war dominated the lives of serf, noble, and clergy alike. Granting her subjects their loyalties, treacheries, and guilty passions, Tuchman re-creates the lives of proud cardinals, university scholars, grocers and clerks, saints and mystics, lawyers and mercenaries, and, dominating all, the knight$1 (Bin all his valor and (3z(Bfurious follies,(3y (Ba (3z(Bterrible worm in an iron cocoon.(3ys
Keywords: France-Nobility; French soldiers; Europe-Middle ages-Ambassadors